Chlorophyll, FDOM and backscatter from ROV survey PS122/4_46-172 on 2020-07-10, survey 1 - Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (In: Anhaus, P et al. (2022): Chlorophyll, FDOM, and backscatter from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.952014, 2022)
Fluorometric data on chlorophyll a concentration, Fluorescent Dissolved Organic Matter (FDOM) concentration, and optical backscatter were measured by a triplet fluorometer (ECO-Puck BBFL2SSC, Wetlabs) attached to a remotely operated vehicle (ROV) during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition between November 2019 and September 2020. Data use manufacturer calibration.
Keywords: BEAST; MOSAiC expedition; Remotely operated vehicle (ROV); Sea ice